2017
DOI: 10.7448/ias.20.1.21610
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of woman‐delivered HIV self‐testing to the male partner, and additional interventions: a qualitative study of antenatal care participants in Malawi

Abstract: Introduction: In the era of ambitious HIV targets, novel HIV testing models are required for hard-to-reach groups such as men, who remain underserved by existing services. Pregnancy presents a unique opportunity for partners to test for HIV, as many pregnant women will attend antenatal care (ANC). We describe the views of pregnant women and their male partners on HIV self-test kits that are woman-delivered, alone or with an additional intervention.Methods: A formative qualitative study to inform the design of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
124
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(138 citation statements)
references
References 35 publications
9
124
5
Order By: Relevance
“…The agenda, which was in part funded by other partners, included formative research and accuracy studies to establish that HIVST was acceptable, safe, and could be correctly performed by priority populations . Further studies tested user preferences and established simple distribution models aimed at using HIVST for maximum public health impact . Data from these early distribution models informed costing and cost‐effectiveness studies to establish the evidence for HIVST scalability and sustainability .…”
Section: Discussionmentioning
confidence: 99%
“…The agenda, which was in part funded by other partners, included formative research and accuracy studies to establish that HIVST was acceptable, safe, and could be correctly performed by priority populations . Further studies tested user preferences and established simple distribution models aimed at using HIVST for maximum public health impact . Data from these early distribution models informed costing and cost‐effectiveness studies to establish the evidence for HIVST scalability and sustainability .…”
Section: Discussionmentioning
confidence: 99%
“…HIV self‐testing (HIVST) can increase HIV testing coverage and frequency . Several studies in Malawi have shown HIVST to be highly acceptable and able to reach first‐time testers, young people (aged 16 to 25), men and couples and partners , with acceptable linkage into facility‐based services when combined with facilitated linkage strategies . As with any form of HIV testing, however, potential social harms (SHs) must be anticipated and mitigated .…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of literature on oral HIV self-testing (HIVST) suggests that it can help to reach people that were not previously targeted by conventional HIV-testing approaches, including male partners and couples [13]. A recent systematic review and meta-analysis that examined the effects of HIVST compared with standard HIV-testing services found that HIVST not only doubled uptake of testing among men but also improved HIV-testing frequency particularly among men who have sex with men [4].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis that examined the effects of HIVST compared with standard HIV-testing services found that HIVST not only doubled uptake of testing among men but also improved HIV-testing frequency particularly among men who have sex with men [4]. Studies conducted in Kenya [2,3,5] and Malawi [1,6] suggest that distribution of HIVST kits to male partners through female partners is an acceptable approach that provides an opportunity for men to test for HIV without necessarily traveling to a health facility. This may overcome the barriers related to lack of time or traveling to a health facility (which men presume to be a women’s preserve) to test for HIV [7,8].…”
Section: Introductionmentioning
confidence: 99%